Micropropagation of Gynostemma pentaphyllum by internode culture techniques - Khai, Pham Cao; Minh, Tran Van (Vietnam Journal of Biotechnology, 2018)
Gynostemma pentaphyllum is a rarely valuable medicinal plant that people has been traditionally used for disease treatment in a long time. The modern medical studies have also shown that it exhibits a variety of pharmacological properties including anti-inflammatory, antioxidative, lipid metabolism regulatory, antiproliferative, neuroprotective and anxiolytic activities. However, conservation and exploiting this medicinal plant were not managed properly and studies of biotechnology on this medicinal plant were till limited. Therefore, the application of plant cell biotechnology in conservation and development of G. pentaphyllum is necessary. The internode segments of G. pentaphyllum were sterilized with diluted solution of javel (50%) for 20 minutes. The rate of sterile explants reached to 73.33%. In vitro shoots tips and cutting stem segments of G. pentaphyllum were used as explants and cultured on MS medium supplemented with BA (0.1; 0.5; 1.0; 1.5; 2.0 mg/L) combined with NAA (0; 0.1; 0.2; 0.3 mg/L) for shoot proliferation. After 6 weeks, new shoots were generated and the MS medium containing 1.0 mg/L BA and 0.1 mg/L NAA gave the highest shoot induction (6.8 shoots/explant). To determine the mineral media suitable for growth of G. pentaphyllum, regenerated shoots were cultured on different mineral media. The MS ½ medium was suitable for growth of shoots with 5.2 cm height and 4.0 leaves/plantlet. For root induction, the MS ½ medium supplemented with 0.25 mg/L IBA was optimal, the root length could be in 7.6 cm in this medium. This system could be utilized for large-scale multiplication of G. pentaphyllum.